2013
DOI: 10.3109/09513590.2012.743020
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and clinical effects of myo-inositol administration in polycystic ovary syndrome. A randomized study

Abstract: MYO administration improves reproductive axis functioning in PCOS patients reducing the hyperinsulinemic state that affects LH secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 24 publications
3
92
3
7
Order By: Relevance
“…Artini et al 8 found that myo-inositol treatment showed significantly lower Testosterone (2.3 nmol/liter vs. 3.4 nmol/liter; 95% CI = 0.07 and 2.1, respectively; P >0.04), similarly to our study. Zacche 5 also showed decrease in testosterone and LH levels after treatment with myoinositol.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Artini et al 8 found that myo-inositol treatment showed significantly lower Testosterone (2.3 nmol/liter vs. 3.4 nmol/liter; 95% CI = 0.07 and 2.1, respectively; P >0.04), similarly to our study. Zacche 5 also showed decrease in testosterone and LH levels after treatment with myoinositol.…”
Section: Discussionsupporting
confidence: 79%
“…WHR did not decrease significantly in myoinositol group (Table 3). This was in contrast to study by Constantino et al 7 Artini et al 8 found that, in consideration of baseline fasting insulin levels, myo-inositol treatment induced similar changes in both groups but only patients in myoinositol group demonstrated significant reduction in fasting insulin levels (20.3 ± 1.8 to 12.9 ± 1.8 µU/mL, P <0.00001).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Following the same fashion, recent studies showed the positive effect on hormonal functions and on insulin sensitivity in target tissues of PCOS subjects [15]. Myo-Ins seems to play a crucial role in oocytes, representing about 99% of inositol intracellular pool [2].…”
Section: Expert Opinionmentioning
confidence: 92%
“…The beneficial effects of inositol have been also proved on metabolic and hormonal parameters in insulin-resistant women. Indeed, a significant improvement of typical hormonal parameters was observed in PCOS women after MI treatment: decreased LH, FSH, and testosterone circulation levels, and increased SHBG, estrogens and progesterone circulating levels [81][82][83]. Insulin peripheral sensitivity was improved(reduced HOMA-IR index and/or reduction of the AUC of glucose and insulin during an oral glucose tolerance test) as well as markers of cardiovascular risk with a decrement in systolic and diastolic blood pressure, a decrease in plasma triglycerides, an increased in HDL cholesterol, and a decrease in LDL and total cholesterol concentrations [84,85].…”
Section: Inositol In Human Reproductionmentioning
confidence: 99%